1990
DOI: 10.1136/jmg.27.5.281
|View full text |Cite
|
Sign up to set email alerts
|

A linkage study of a large pedigree with X linked centronuclear myopathy.

Abstract: Centronuclear myopathy (CNM) is a muscle wasting disorder that occurs in three distinct forms. Previous studies have shown linkage between the X linked form of the disease and the Xq28 probes ST14, DX13, and F8C. Our study on a previously unreported, three generation, X linked CNM family confirms linkage between these markers and the CNM locus (Z=3.21, 0=00). However, results from the laboratory of J-L Mandel (Samson and Hanover, personal communication) on a number of X linked CNM families exclude genetic link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 6 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…Previous studies have shown evidence for linkage between MTM1 and several polymorphic DNA markers at Xq28 (Thomas et al 1987;Darnfors et al 1990;Lehesjoki et al 1990;Starr et al 1990; Thomas et al 1990;Liechti-Gallati et al 1991;Janssen et al 1994). A more precise relative localization of the MTM1 gene and other marker loci was achieved after analysis of key recombinations (Dahl et al 1994) and an interstitial deletion associated with MTM1 (Dahl et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown evidence for linkage between MTM1 and several polymorphic DNA markers at Xq28 (Thomas et al 1987;Darnfors et al 1990;Lehesjoki et al 1990;Starr et al 1990; Thomas et al 1990;Liechti-Gallati et al 1991;Janssen et al 1994). A more precise relative localization of the MTM1 gene and other marker loci was achieved after analysis of key recombinations (Dahl et al 1994) and an interstitial deletion associated with MTM1 (Dahl et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Linkage studies have mapped the XLMTM locus (MTM1) to Xq28 [10–12], and the MTM1 gene was subsequently isolated by positional cloning [13]. The gene codes for a protein named myotubularin, which appears to be ubiquitously expressed, with a 3.9 kb transcript detected in all adult and fetal tissues studied.…”
mentioning
confidence: 99%
“…The MTM1 gene has been mapped to the Xq28 region of the long arm of the X chromosome (Darnfors et al 1990;Janssen et al 1994;Lehesjoki et al 1990;Liechti-Gallati et al 1991;Starr et al 1990;Thomas et al 1987Thomas et al , 1990. Subsequent genetic linkage studies have refined its localization, reducing the candidate region to a 430-kb interval, distal to DXS304 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent genetic linkage studies have confirmed the assignment of the gene (Darnfors et al 1990;Janssen et al 1994;Lehesjoki et al 1990;Liechti-Gallati et al 1991;Starr et al 1990), refining the candidate region subsequently to a 600-kb interval (Dahl et al 1995) and narrowing it recently to about 430 kb, distal to DXS304 ; Fig. 1).…”
Section: Introductionmentioning
confidence: 99%